Faktor-Faktor yang Mempengaruhi Permintaan Impor Tekstil dan produk Tekstil (TPT) China di Jawa Timur Terkait ASEAN-China Free Trade Area (ACAFTA) Tahun 2010-2013 - Muliawati, Riski (Global and Policy Journal of International Relations, 2016)
ABSTRACTThis study examines the factors that influence the demand for the imports of the textiles and textile products (TPT) from China in the East Java, Indonesia. This research is based on the implementation of the ASEAN-China Free Trade Area (ACFTA), applied to the ASEAN members and China. The implementation of tariff exemption between ASEAN-6 and China under the ACFTA, entered into force in 2010. The tariff exemption is being imposed to some of the TPT products under the category of Normal Track that affected the demand for Chinese textile imports in the East Java. The main problems to be discussed on this study are the factors that influence the demand for Chinese textile imports in East Java in regards to the ACFTA. This study uses the theory of the Free Trade Area (FTA), consumption theory, the theory of aggregate demand, business strategy, pricing strategy, the strategy of imitation, and the concept of imports. Based on the findings of the research, this research concludes that the factors affecting the demand for Chinese textile imports in East Java are divided into the external factors and internal factors. The External factors is the impact of the tariff-free implementation of ACFTA and the business strategies of China. While the internal factors comes from the purchasing power of the East Java, which can be observed through factors such as the prices, consumption, and average incomes.Keywords: ASEAN-China Free Trade Area (ACFTA), business strategy, import demand, TPT East JavaDOI : https://doi.org/10.33005/jgp.v4i01.1928